Economic Growth and Poverty Reduction: Evidence from Kazakhstan - Pradeep Agrawal (Asian Development Review, 2007)
This paper empirically examines the relation between economic growth and poverty alleviation in the case of Kazakhstan using province-level data. It shows that provinces with higher growth rates achieved faster decline in poverty. This happened largely through growth, which led to increased employment and higher real wages and contributed significantly to poverty reduction. Rapidly increasing oil revenues since 1998 have helped significantly raise both gross domestic product growth and government revenue in Kazakhstan. Part of the oil fund was used to fund a pension and social protection program that has helped reduce poverty. However, expenditure on other social sectors like education and health has not increased much and needs more support. It is also shown empirically that increased government expenditure on social sectors did contribute significantly to poverty alleviation. This suggests that both rapid economic growth and enhanced government support for the social sectors are helpful in reducing poverty.